Experience of mental health in women with Polycystic Ovary Syndrome: a descriptive phenomenological study - Guangpeng Wang; Xueyan Liu; Shujuan Zhu; Jun Lei (Taylor & Francis Group, 2023)
Purpose: This study aims to investigate the experiences, emotional coping strategies, and help-seeking needs of women with PCOS from their perspective, considering common psychological issues such as stress, anxiety, and depression that are prevalent among individuals with PCOS. Materials and Methods: The study recruited 14 women with PCOS for semi-structured interviews between October and November 2022, using a descriptive phenomenology method design. The interviews were analyzed using NVivo 12 software. Results: Four themes and eleven subthemes were derived from the semi-structured interviews: (1) Negative Mental Health Status; (2) Four Patterns of Emotion Regulation; (3) The Psychological Double-Edged Sword: Family Social Network; (4) Strong Demands for Psychological Counseling and Lifestyle Guidance. Conclusion: The study suggests that interventions should focus on fostering internalized self-efficacy and emotional expression, promoting constructive familial support, and providing psychological counseling and lifestyle recommendations to alleviate psychological distress experienced by women with PCOS.